Hydrothermal zinc oxide nanostructures: geometry control and narrow band UV emission. Issue 1 (1st March 2022) - Kadinskaya, S A; Kondratev, V M; Kindyushov, I K; Labzovskaya, M E; Novikov, B V; Shtrom, I V; Lihachev, A I; Nashchekin, A V; Bolshakov, A D
Abstract: In this work we study zinc oxide nanostructures of various geometries synthesized via the hydrothermal technique on Si (111) substrate. We demonstrate capabilities of the growth protocol for control over the morphology of nanostructures varying from nanowires to hexapods. The obtained samples were studied by photoluminescence spectroscopy to demonstrate a very narrow spontaneous emission near 370 nm. Despite cheap and feasible fabrication, the obtained nanostructures possess high crystallinity confirmed by the absence of typical for ZnO wide emission band in the visible region, related with the structure imperfections. This property together with the capabilities of the geometrical control over the nanostructures unveil perspectives of the reported approach for future UV photonic applications.